Penerapan Pembelajaran Berdiferensiasi Pada Anak Usia Dini Di Paud Al-Anisa Kota Bengkulu - Saputri, Gita; Nurwita, Syisva; Asnawati, Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the Implementation of Differentiated Learning in Early Childhood at Paud Al-Anisa, Bengkulu City. This research method is descriptive qualitative. Qualitative research is research that produces descriptive data processing. Data collection used in the study was by using observation, interviews, and documentation with three data analyzes, namely data reduction, data presentation and conclusions. The results of this study indicate that the implementation of differentiated learning in early childhood, namely: 1) content is the material that will be taught that will be understood, appreciated, and learned by children, 2) the process is an effort where children collect information and learn it, 3) the product is the result of learning how to evaluate children's knowledge, abilities, and understanding after completing one learning, 4) the learning environment of the class structure personally, socially, and physically.